2017
DOI: 10.4049/jimmunol.1700498
|View full text |Cite
|
Sign up to set email alerts
|

IL-4/IL-13 Signaling Inhibits the Potential of Early Thymic Progenitors To Commit to the T Cell Lineage

Abstract: Early thymic progenitors (ETPs) are endowed with diverse potencies and can give rise to myeloid and lymphoid lineage progenitors. How the thymic environment guides ETP commitment and maturation towards a specific lineage remains obscure. We have previously shown that ETPs expressing the heteroreceptor (HR) comprising IL-4 receptor alpha (IL-4Rα) and IL-13 receptor alpha 1 (IL-13Rα1) give rise to myeloid but not T cells. Here we show that signaling through the HR inhibits ETP maturation to the T cell lineage bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…39) IL-4 is one of the main Th2-producing cytokines that plays a crucial role in inflammatory events and promotes differentiation and proliferation of Th2 cells. 40) Recent studies have indicated that IL-4 in the thymus inhibits the commitment of early thymic progenitor cells to T cell lineage as well as the differentiation of CD8 + cytotoxic T cells. 41,42) IL-4 expression in the thymus may be strictly controlled to avoid its unpleasant effect on T cell development.…”
Section: Diet-restriction-induced Thymic Involution Involves the Polamentioning
confidence: 99%
“…39) IL-4 is one of the main Th2-producing cytokines that plays a crucial role in inflammatory events and promotes differentiation and proliferation of Th2 cells. 40) Recent studies have indicated that IL-4 in the thymus inhibits the commitment of early thymic progenitor cells to T cell lineage as well as the differentiation of CD8 + cytotoxic T cells. 41,42) IL-4 expression in the thymus may be strictly controlled to avoid its unpleasant effect on T cell development.…”
Section: Diet-restriction-induced Thymic Involution Involves the Polamentioning
confidence: 99%
“…These CD8 “memory-like” T cells have important roles in early defenses, particularly in situations of chronic viral infection 6 , 7 . Thymic steady-state IL-4 also drives the acquisition of an activated/memory-like phenotype by Foxp3 + regulatory T cells 8 , the production of chemokines by thymic dendritic cells 2 , the thymic exit of mature “conventional” T cells 9 and also perhaps the commitment of early thymic progenitors to the T cell lineage 10 . Additionally, RANKL-expressing CD44 − thymic iNKT cells (which are preferentially enriched for iNKT2 and iNKT17 cells) regulate the differentiation of Aire + MHC class II + medullary thymic epithelial cells 11 that are involved in clonal deletion of self-reactive T cells 12 and Treg maturation 13 .…”
Section: Introductionmentioning
confidence: 99%
“…We took advantage of KEGG analyses to point out that hsa_circ_0005519 could be related to the MAPK and JAK‐STAT signalling pathways in asthma. IL‐6 and IL‐13, which are important inflammatory mediators in asthma as mentioned above, play a role in T cell differentiation and activation by MAPK or JAK‐STAT signalling pathways . And accumulating evidence indicates that these two signalling pathways are involved in regulating cytokines such as IL‐6 and IL‐13 in asthma inflammation .…”
Section: Discussionmentioning
confidence: 97%